STUDI PEDAGOGIK EMPIRIS : PERAN PRANATA PENDIDIKAN DALAM DINAMIKA BUDAYA DAN STRUKTUR ORGANISASI - Fajriani, Putri; Babang Robandi; Resti Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education is an important aspect in forming individuals who are able to contribute actively to society. This research aims to analyze the role of the three educational institutions of family, school and community in a cultural and organizational context. The family, as the first institution, functions to shape students' moral, social and religious values. Schools play the role of continuing family education formally and systematically, while society supports education through preserving culture and providing resources. through a qualitative descriptive approach, this research also explores the influence of culture on the education system in several countries, such as Indonesia, Japan and Finland. The research results show that educational success is greatly influenced by the synergy between these three institutions, as well as adaptation to local values. In Indonesia, education faces the challenge of cultural diversity, while Japan and Finland show excellence through discipline and the principle of equality. this research concludes that collaboration between families, schools and communities is very important to create an education system that is locally relevant and globally competitive.